The Influence of Influencers and the Quality of Elformula Skincare Products on Impulsive Buying of Tiktok Consumers in Padang City with Trust as a Mediating Variable - Ezy Rahmadani; Whyosi Septrizola (Journal of Management and Administration Provision, 2025)
Technological progress in the age of globalization has led to notable transformations in human behavior, especially in the adoption of online shopping practices  This research seeks to examine how influencers and product quality affect the impulsive purchasing behavior of TikTok Shop users in Padang City, with trust functioning as a mediating variable. This study is motivated by the growing utilization of social media platforms for digital marketing purposes, particularly TikTok, which combines entertainment with e-commerce features and encourages unplanned, impulsive consumer behavior especially in skincare product categories like Elformula. A quantitative method was employed in this study by distributing surveys to 160 TikTok users who met specific research criteria. The data were obtained through a questionnaire using a Likert scale and analyzed using the Partial Least Squares (PLS) approach via SmartPLS 4 software. The findings indicate that both influencers and product quality positively and significantly influence consumer trust, which in turn has a significant positive impact on impulsive buying behavior. Other important findings suggest that the indirect effect of trust on impulse buying, influencer on impulse buying through trust, and product quality on impulse buying through trust. The conclusion of this study confirmed that marketing strategies through credible influencers and the perception of good product quality played an important role in building consumer confidence, which then triggered spontaneous purchases on the TikTok Shop platform This study is anticipated to offer theoretical contributions to the advancement of consumer behavior research in the digital era, while also providing practical insights for e-commerce marketers and business practitioners in crafting effective marketing communication strategies.